مطالعہ سیرت میں مولانازکریاکاندھلویؒ کامنہج:ایک تجزیاتی مطالعہ: An Analytical Study of Maulana Zakaria Kandhalvi’s Manhaj in the Study of Seerah - Dr Muhammad Inamullah (Al Manhal Research Journal, 2023)
Scholar of the subcontinent, while they have written on other subjects, have written a large number of books and articles on Shamail Nabavi and Khasail Nabavi (peace and blessings of Allah be upon him).Among these scholars,the name of Maulana Muhammad Zakaria Kandhalvi is prominent.He is simultaneously, a Muhadith ,commentator and a biographer. While he has received great accolades from Arab and non Arab scholars for his great books such as Awjaz ul Masalik, Al Abwab waltarajim, lami udurari etc, he also wrote great books on the biography of the prophet (peace and blessing of Allah be upon him). In this regard, some of the books he has written have been published and some have not been published. In this article, along with the introduction of these books, an attempt has been made to clarify their method and services in the biography of the prophet (peace and blessings of Allah be upon him).